Stereotypes, Sex Discrimination and Paranoia - an experimental study - Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2000)
We analyze results from two categories of experiments where the subjects received controlled signals about the sex of their co-players. In a series of Battle of the Sexes experiments the subjects played more hawkish against women than against men. The impact of the sex signal was most pronounced among female subjects. In the second category of experiments we develop a measure of discrimination effects. We then survey discrimination effects across 32 subject groups from Israel, Sweden, UK and USA. The results indicate discrimination against females in experimental bargaining. This discrimination behavior is significant among females but not among males.
Keywords: C78; C91; J71; 330; Sex discrimination; gender differences; bargaining; experiments; coordination